The best life diet - Greene, Bob (Bob W.) (New York : Simon & Schuster Paperbacks, 2009)
Explains how to lose weight permanently in a resource that complements dietary guidelines with dozens of nutritionally balanced recipes.
Includes indexes.
PBK.
Keywords: Weight loss -- Popular works; Reducing diets -- Popular works; Nutrition -- Popular works; Physical fitness -- Popular works; Reducing diets -- Recipes -- Popular works